2022
DOI: 10.1038/s41598-022-06310-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the robust predictor for sepsis based on clustering analysis

Abstract: Sepsis is a life-threatening disorder with high incidence and mortality rate. However, the early detection of sepsis is challenging due to lack of specific marker and various etiology. This study aimed to identify robust risk factors for sepsis via cluster analysis. The integrative task of the automatic platform (i.e., electronic medical record) and the expert domain was performed to compile clinical and medical information for 2,490 sepsis patients and 16,916 health check-up participants. The subjects were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…A recent observational study demonstrated that NLR and IL-6 appeared to be independent predictors of 28-day mortality in septic patients [ 22 ]. Moreover, Jang et al conducted a clustering analysis showing that age, NLR and delta neutrophil index (DNI) were the most robust predictors for sepsis status in all subjects, as well as in cluster-specific groups [ 23 ]. These findings could contribute to suggest a strategy to screen sepsis patients without leukocytosis in the emergency care units.…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…A recent observational study demonstrated that NLR and IL-6 appeared to be independent predictors of 28-day mortality in septic patients [ 22 ]. Moreover, Jang et al conducted a clustering analysis showing that age, NLR and delta neutrophil index (DNI) were the most robust predictors for sepsis status in all subjects, as well as in cluster-specific groups [ 23 ]. These findings could contribute to suggest a strategy to screen sepsis patients without leukocytosis in the emergency care units.…”
Section: Nlr and The Pathophysiology Of Inflammatory Diseasementioning
confidence: 99%
“…In general, CRP is known to have a higher diagnostic accuracy for infection than that of WBC or ESR [ 20 ]. Moreover, a recent study demonstrated that the DNI and NLR are robust predictors of equivocal septic conditions using clustering analysis [ 24 ]. In contrast, the OM group exhibited significantly negative associations only with ESR and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, the proposed prediction model in this study could be combined with the microbiological and clinical outcome profiles in well-designed prospective cohort in the future. By extension, further study based on a clustering analysis method comparing the combined model with pre-existing etiology-based NF classification (type I~IV) is feasible and promising [ 24 , 54 ]. Lastly, we did not consider other comorbidities affecting the infection status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster analysis is a machine learning technique that aims to group observations that are similar within the same cluster. It is a useful tool in infectious disease, analyzing biomarkers and predictors of neonatal sepsis, but to the best of our knowledge, no study has applied it to antibiotic stewardship in LMICs NICU setting [10,11]. The aim of this study was to identify clusters of patients switching between different antibiotic lines and to explore their potential associations with death or severe clinical presentation in terms of RD.…”
Section: Introductionmentioning
confidence: 99%